An Analysis of Five years Neonatal Mortality in NICU of a Tertiary Care Hospital of Rawalpindi 2014-2019 - Rai Muhammad Asghar , Mudassir Sharif , Khalid Saheel , Rai Rijjal Ashraf , Abid Hussain , Rai Muhammad Asghar , Mudassir Sharif , Khalid Saheel , Rai Rijjal Ashraf , Abid Hussain (Journal of Rawalpindi Medical College, 2020)
Objective: This study was done to find out the main causes and magnitude of neonatal mortality in the neonatal intensive care unit (NICU) of Benazir Bhutto Hospital, Rawalpindi over a period of five years. Material and Methods: A hospital-based cross-sectional study was done from June 2014 to July 2019. The registration book of admitted neonates was reviewed by using a checklist to collect data. Data was analyzed in SPSS 24 for descriptive and bi-variate analysis applying the chi-square test and presented in text, frequencies, tables, and percentages. Results: The study assessed a total of 24,459 neonates admitted to the NICU at Benazir Bhutto Hospital over a span of five years (June 2014 to July 2019). The mean birth weight was 2432 grams ± 740 g (range: Between 800 and 6000 g). Male neonates accounted for 59.8% with male to female ratio of 1.5:1. 67.5% male neonates and 32.5% female neonates expired. Overall 19,832 neonates (81.1%) were discharged, while 4636 (18.9%) died, making a Neonatal Mortality Rate of 18.9% (189 per 1000 admissions). 86.21% of these deaths were early neonatal that occurred in the first week of life. The causes of death were pre-maturity/ low birth weight (LBW), suspected sepsis, birth asphyxia, neonatal jaundice, and meconium aspiration syndrome, accounting for 32%, 31%, 30%, 4%, and 3% respectively. Conclusion: In our NICU the neonatal mortality is high with prematurity/low birth weight (LBW), birth asphyxia (BA), neonatal jaundice (NNJ), and meconium aspiration syndrome (MAS) accounting for most of the deaths. These deaths are largely preventable with better antenatal, perinatal, and neonatal care.